Relevance of muscle biopsies in the neonatal and early infantile period: a 52 years retrospective study in the gene-sequencing era - Bui, Mai Thao; Fernández-Eulate, Gorka; Evangelista, Teresinha; Lacène, Emmanuelle; Brochier, Guy; Labasse, Clémence; Madelaine, Angéline; Chanut, Anaïs; Beuvin, Maud; Borsato-Levy, Favienne; Biancalana, Valérie; Barcia, Giulia; et al. (Acta neuropathologica communications, 2024)
Neuromuscular disorders (NMD) with neonatal or early infantile onset are usually severe and differ in symptoms, complications, and treatment options. The establishment of a diagnosis relies on the combination of clinical examination, morphological analyses of muscle biopsies, and genetic investigations. Here, we re-evaluated and classified a unique collection of 535 muscle biopsies from NMD infants aged 0–6 months examined over a period of 52 years. We aimed to assess the importance and contribution of morphological muscle biopsy analyses for the establishment of a precise and accurate molecular diagnosis. Altogether, 82% of the biopsies showed typical structural myofiber anomalies highly suggestive of specific NMD classes (congenital myopathies, metabolic myopathies, lower motor neuron (LMN) and neuromuscular junction (NMJ) disorders, muscular dystrophies, inflammatory myopathies), while the remaining 18% showed no or only non-specific histological abnormalities. The diagnostic success rate differed among the NMD classes and was particularly high for congenital myopathies as illustrated by the identification of causative genes in 61% of cases. This is essentially due to the presence of characteristic histopathological hallmarks on biopsies visible by light or electron microscopy often pointing to specific genes. In contrast, metabolic myopathies commonly displayed non-specific features on muscle sections, led to the identification of causative genes in only 19% of the patients, and typically required additional enzymatic tests to establish a more precise diagnosis. The evolution of sequencing technologies fundamentally improved molecular diagnosis and also shifted the relevance of muscle biopsies within the diagnostic process. Depending on the clinical presentation of the patients, direct gene or panel sequencing may be the preferred method nowadays. However, histological and ultrastructural examinations of muscle sections are still frequently useful and can constitute an elemental step in the diagnostic process—either by directing purposeful gene sequencing or pointing to genes and pathogenic variants identified by next-generation sequencing (NGS), or by complementing clinical findings and biochemical analysis methods.